2000
DOI: 10.1074/jbc.m007775200
|View full text |Cite
|
Sign up to set email alerts
|

P2Y2 Purinergic and M3 Muscarinic Acetylcholine Receptors Activate Different Phospholipase C-β Isoforms That Are Uniquely Susceptible to Protein Kinase C-dependent Phosphorylation and Inactivation

Abstract: Activation of phospholipase C-beta (PLC-beta) by G protein-coupled receptors typically results in rapid but transient second messenger generation. Although PLC-beta deactivation may contribute to the transient nature of this response, the mechanisms governing PLC-beta deactivation are poorly characterized. We investigated the involvement of protein kinase C (PKC) in the termination of PLC-beta activation induced by endogenous P2Y(2) purinergic receptors and transfected M(3) muscarinic acetylcholine receptors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 29 publications
5
38
0
Order By: Relevance
“…In the latter two tissues, volume-sensitive PLC activation appears to involve autocrine stimulation of P2Y purinergic receptors. Although it is known that P2Y receptors can activate PLC␤ and PLC␥ (23,24), the identity of PLC isoforms that mediate volume-sensitive purinergic Ca 2ϩ signaling has not been elucidated. As we have shown that swelling-mediated increases in [Ca 2ϩ ] i in HTC cells are independent of purinergic receptor stimulation (4), it is likely that distinct mechanisms are involved in volume-sensitive PLC activation in liver.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter two tissues, volume-sensitive PLC activation appears to involve autocrine stimulation of P2Y purinergic receptors. Although it is known that P2Y receptors can activate PLC␤ and PLC␥ (23,24), the identity of PLC isoforms that mediate volume-sensitive purinergic Ca 2ϩ signaling has not been elucidated. As we have shown that swelling-mediated increases in [Ca 2ϩ ] i in HTC cells are independent of purinergic receptor stimulation (4), it is likely that distinct mechanisms are involved in volume-sensitive PLC activation in liver.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, densitometry showed that M3 muscarinic receptor expression actually was increased by 298% ± 9% relative to normal controls (P < 0.0005, Figure 5B), consistent with previous reports. 8 The α subunits of the G q and G 11 G proteins, which are coupled to the M3 muscarinic receptor, 19 were studied in normal and bile duct-ligated biliary epithelia by the same technique. The amounts of the subunits were similar under both conditions ( Figure 5C and D); cells after BDL expressed 93.2% ± 2.1% of the amount of Gα q /α 11 expressed by normal bile duct cells (P > 0.3).…”
Section: Upstream Components Of the Ca 2+ Signaling Pathway Are Presementioning
confidence: 99%
“…These steps include binding of ACh to the M3 muscarinic receptor, activation of an associated G protein, and then PLCβ activation. 19 To determine whether any of these upstream signal transduction events also are affected by BDL, we examined expression of the M3 muscarinic ACh receptor, Gα q /α 11 protein, and PLCβ3. Immunoblot analysis showed that M3 muscarinic receptor expression was not decreased after BDL ( Figure 5A).…”
Section: Upstream Components Of the Ca 2+ Signaling Pathway Are Presementioning
confidence: 99%
“…Quantitative Phosphorylation Assay-Quantitative phosphorylation assay was designed based on the established protocols described elsewhere (51,52,66,67). Briefly, the DJM-1 cells were grown to ϳ75% confluence in 75-cm 2 flasks in KGM containing 0.09 mM Ca 2ϩ without hydrocortisone supplement (Clonetics, Walkerville, MD) at 37°C in a humid 5% CO 2 incubator, and then incubated for additional 48 h in minimal essential medium containing 10% dialyzed fetal bovine serum, 1.8 mM Ca 2ϩ , and 10 ng/ml epidermal growth factor (all from Invitrogen).…”
Section: Pemphigus and Control Igg Fractions-mentioning
confidence: 99%